2018
DOI: 10.1159/000489015
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns for Chronic Respiratory Diseases in the Asia-Pacific Region: A Cross-Sectional Observational Study

Abstract: Background: Allergic rhinitis (AR), asthma, chronic obstructive pulmonary disease (COPD), and rhinosinusitis are common and little studied in the Asia-Pacific region. Objectives: We sought to investigate real-world practice patterns for these respiratory diseases in India, Korea, Malaysia, Singapore, Taiwan, and Thailand. Methods: This cross-sectional observational study enrolled adults (age ≥18 years) presenting to general practitioners (GP) or specialists for physician-diagnosed AR, asthma, COPD, or rhinosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…6,7 A cross-sectional observational study conducted in six countries from the Asia-Pacific region demonstrated considerable healthcare resource utilization (HCRU) and associated cost burden owing to chronic respiratory diseases (combined: asthma, allergic rhinitis, chronic obstructive pulmonary disease (COPD), and rhinosinusitis). 8 The socioeconomic burden for asthma, specifically in Asia, consists of individual reports from Thailand, South Korea, Singapore, Taiwan, and India. 9–14 However, data focusing on HCRU in asthma patients from Japan are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 A cross-sectional observational study conducted in six countries from the Asia-Pacific region demonstrated considerable healthcare resource utilization (HCRU) and associated cost burden owing to chronic respiratory diseases (combined: asthma, allergic rhinitis, chronic obstructive pulmonary disease (COPD), and rhinosinusitis). 8 The socioeconomic burden for asthma, specifically in Asia, consists of individual reports from Thailand, South Korea, Singapore, Taiwan, and India. 9–14 However, data focusing on HCRU in asthma patients from Japan are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In Japanese students, both seasonal and, in particular, perennial allergic rhinitis are significantly associated with a current wheeze [12]. A cross-sectional, observational study investigating real-world practice patterns for allergic rhinitis, asthma, chronic obstructive pulmonary disease, and rhinosinusitis in India, Korea, Malaysia, Singapore, Taiwan, and Thailand provided regional and country-specific information and suggested different practice patterns between specialists and general practitioners, and highlighted the substantial disease burden [13]. …”
Section: Characterization Of Subgroups Of Allergic Rhinitismentioning
confidence: 99%
“…[ 3 4 ] Although guidelines for the management of COPD are available for more than a decade,[ 5 ] a recent study indicated that the practice pattern is significantly different among physicians. [ 6 ] In hospital settings, a nurse-led model of COPD management has been proposed. [ 7 ] However, the evidence on the effectiveness of such models is not promising.…”
Section: Introductionmentioning
confidence: 99%